The behavior of golf ball putting on artificial turf - Drane, P.; Duffy, M.; Fournier, J.; Sherwood, J.; Breed, M. (Procedia Engineering, 2014)
The putting of a golf ball requires control of the speed and direction and an understanding of the interaction between the ball and the putting green by the golfer. The putt can involve a combination of the ball flying over, skidding across, and rolling on the putting green. This study used finite element analysis as a tool to investigate these behaviors, and this paper documents the results for putts with different initial velocities. The finite element analyses were performed in LS-DYNA using a viscoelastic material model for the turf and an elastic material for the golf ball and club head. A high-grade artificial putting turf was characterized by its compressive stiffness in a Universal Testing Machine and displacement of a golf ball resting on turf. The static and dynamic friction between the golf ball and artificial turf were investigated. The ball velocity and deceleration resulting from different putts were examined to help in the characterization of the behavior of the turf. The finite element model will be used in future studies to determine the optimal putter loft and rise angles to achieve consistent putts.